Report of the Working Group on Animal Husbandry (Including Poultry) and Dairying for Formulation of the Eighth Five Year Plan - Planning Commission (Planning Commission, 1989)
In pursuance of a decision taken in the meeting of the Steering Group of the Planning Commission on Agriculture & Allied Sectors held on 15th July 1988, a Working Group on Animal Husbandry (including Poultry) and Dairying was set up under the Chairmanship of Dr V Kurien, Chairman, National Dairy Development Board, for the formulation of the Eighth Five Year Plan.
Planning Commission
Planning Commission